Evaluation of Disk Diffusion and Etest Compared to Broth Microdilution for Antifungal Susceptibility Testing of Posaconazole against Clinical Isolates of Filamentous Fungi - Messer, Shawn A. (American Society for Microbiology, 2007)
We performed Etest, disk diffusion, and broth microdilution susceptibility testing of posaconazole against 146 clinical isolates of filamentous fungi. By using provisional breakpoints for comparison purposes only, categorical agreement between the results of the agar-based methods and those of broth microdilution were 96 to 98%, with no very major errors. These agar-based methods hold promise as simple and reliable methods for determining the posaconazole susceptibilities of filamentous fungi.